2019
DOI: 10.21315/aamjaf2019.15.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Higher Co-Moments and Downside Beta in Asset Pricing

Abstract: The Capital Asset Pricing Model (CAPM) assumes a linear relationship between an asset's return and financial market. However, empirical invalidity of linearity of returns has given birth to other CAPM models. Therefore, this study aims to examine the implication of preference by a risk-averse investor for higher moments and downside risk as investors are assumed to be prudent, temperate and cautious and prefer firms with negative coskewness, positive co-kurtosis, and downside risk as they yield higher risk pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
2
2
0
Order By: Relevance
“…Downside beta turned out to be a more appropriate measure of systematic risk than the conventional beta coefficient in explaining the cross-section of portfolio returns. This conclusion was supported by, among others, Estrada (2007), Ang et al (2006) and Chhapra & Kashif (2019). They confirmed that downside beta is a better predictor of portfolio returns than conventional beta.…”
Section: Research Contributionsupporting
confidence: 52%
“…Downside beta turned out to be a more appropriate measure of systematic risk than the conventional beta coefficient in explaining the cross-section of portfolio returns. This conclusion was supported by, among others, Estrada (2007), Ang et al (2006) and Chhapra & Kashif (2019). They confirmed that downside beta is a better predictor of portfolio returns than conventional beta.…”
Section: Research Contributionsupporting
confidence: 52%
“…On the other hand, Hung et al (2004) have empirically proved that comoments were insignificant. Similar conclusions regarding co-kurtosis emerge from research on the Karachi stock exchange (Javid, 2009;Chhapra & Kashif, 2019). Ambiguous results regarding the valuation of higher moments were reported by Akbar and Nguyen (2016).…”
Section: Literature Reviewsupporting
confidence: 69%
“…Moreover, they argued that the relationship between downside risk and future returns was strongly negative at the portfolio level but relatively flat at the stock index level. Chhapra & Kashif (2019) employed a dataset of 901 firms on the Pakistan Stock Exchange from 2000 to 2016 to investigate the implications of risk-averse investor preferences for higher moments and downside risk. They argued that investors favored firms exhibiting negative co-skewness, positive co-kurtosis, and downside risk because they yielded a higher risk premium.…”
Section: Literature Reviewmentioning
confidence: 99%